Lettere a Mario Cerroni - De Libero, Libero 1906-1981 (Ed. dell'Arengario, 1999)
Unedited letters on the meaning and reasons of poems written 1951-1952 by the author to the poet and Communist militant M. Cerroni (1921-1957).
Keywords: Cerroni, Mario <1921-1957> -- Correspondence; De Libero, Libero -- Correspondence; Geschichte 1900-2000; Poets, Italian -- 20th century -- Correspondence